Robust anticancer efficacy of Naja haje venom-loaded silica nanoparticles against triple-negative breast cancer xenografts in a preclinical rat model - Nabil A. Soliman; Amr A. Shalaby; Heba Allah Mohamed; Sara M. Abdelkarem Alashqar; Mohamed Ahmed Ammar (Open Veterinary Journal)
Background: Breast cancer, a prevalent disease affecting women globally, is particularly aggressive and has limited treatment options.